2017
DOI: 10.1080/15563650.2017.1339887
|View full text |Cite
|
Sign up to set email alerts
|

The standard treatment protocol for paracetamol poisoning may be inadequate following overdose with modified release formulation: a pharmacokinetic and clinical analysis of 53 cases

Abstract: The pharmacokinetic and clinical analysis showed that the standard treatment protocol, including risk assessment and NAC regimen, used for IR paracetamol poisoning not appear suitable for MR formulation. Individual and tailored treatment may be valuable but further studies are warranted to determine optimal regimen of overdoses with MR formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the previous guidelines, management was very similar to that for immediate release paracetamol. However, evidence from case series from Australia and Europe has shown that this approach appears inadequate . Patients developed acute liver injury despite standard treatment such as early acetylcysteine and decontamination.…”
Section: Modified Release Paracetamol Ingestionsmentioning
confidence: 99%
“…In the previous guidelines, management was very similar to that for immediate release paracetamol. However, evidence from case series from Australia and Europe has shown that this approach appears inadequate . Patients developed acute liver injury despite standard treatment such as early acetylcysteine and decontamination.…”
Section: Modified Release Paracetamol Ingestionsmentioning
confidence: 99%
“…Although it is safe to use in clinical doses in human medicine, the studies shows that toxicity caused by overdose APAP may cause liver and kidney damage and even deaths may develop [1,2]. Because paracetamol is one of the commonest drugs taken in overdose and involved in deliberate self-poisoning in many countries [3][4][5]. At therapeutic doses, the majority of APAP is metabolized by sulphation (20-30%) and glucuronidation (45-55%), while 5-9% is converted to N-acetyl-para-benzoqinonimine (NAPQI), a highly reactive metabolite by cytochrome p450 (CYP 450) enzymes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Modified-release products use a different method of prolonging acetaminophen absorption. These products have been associated with markedly delayed absorption and unexpected toxicity . These products are marketed in Europe and Australia but not in the US or Canada, to our knowledge.…”
Section: Discussionmentioning
confidence: 99%